Reflections on Critical Education in the Practice of Primary School Teacher Professionalism in Surakarta - Apriliani, Elina Intan; Belannisa, Kartika; Fauziyah, Nur Lina; Musfiroh, Musfiroh; Al abdillah, Pipuk Zainita Choirun Nisa (CV. Creative Tugu Pena, 2023)
This research explores the role of digital technology, critical education, and the practice of professionalism of grade 3 teachers in the digital era, focusing on the context of SD Djamaatul Ichwan Surakarta. Through a qualitative approach, data was collected through in-depth interviews with grade 3 teachers and observation of learning activities. The results showed that digital technology positively impacts student learning, but needs teacher supervision so that students are not exposed to negative content. Critical education is integrated in the curriculum with diverse approaches, creating a holistic learning environment. Challenges in implementing critical education were identified, requiring teacher awareness in the presentation of materials. School institutions provide physical support and regular training. Integrating technology and critical education creates a learning environment supporting the development of students' critical skills. The results of this study are expected to contribute to the development of education in the digital era. Keywords: Critical Education, Teacher Professionalism, Primary School